Conceptual design for methanol steam reforming in serial packed-bed reactors and membrane filters: Economic and environmental perspectives. (15th February 2022) - Byun, Manhee; Kim, Heehyang; Lee, Hyunjun; Lim, Dongjun; Lim, Hankwon
Abstract: Methanol steam reforming (MSR) in packed-bed reactors (PBRs) with membrane filters has emerged as promising hydrogen (H2 ) production system to overcome limitations of conventional membrane reactor (MR), which has H2 permeable membrane inside. In this study, techno-economic analysis is conducted based on results of process simulation using Aspen HYSYS® to assess technical and economic feasibility of MSR in systems of different number of PBRs and membrane filters and key economic parameters are presented. Also, effects of techno-economic parameters of reaction temperature, H2 permeance, and the number of PBRs and membrane filters on a unit H2 production cost are investigated, individually and comprehensively, in the ranges from 448 to 513 K, from 5 × 10 − 6 to 5 × 10 − 5 mol m −2 s −1 Pa −1, and one to four PBRs with zero to three membrane filters. Based on techno-economic analysis results, regression function for the unit H2 production cost is achieved and optimization of operating conditions using GAMS© is conducted showing the minimum unit H2 production cost of 7.03 kgH2 −1 and optimized conditions of 513 K, 5 × 10 − 5 mol m −2 s −1 Pa −1, and two PBRs with one membrane filter. In addition, to investigate environmental feasibility, carbon footprint analysis is performed with comparing CO2 emissions according to techno-economic parameters. Graphical abstract: Image 1 Highlights: Process simulation model for multi-stage packed-bed reactors and membrane filters constructed. Economic analysis and carbon footprint analysis with various conditions of techno-economic parameters conducted. Optimum conditions of 513 K, 5 × 10 − 5 mol m −2 s −1 Pa −1, and two PBRs with one membrane filter confirmed. Minimum unit H2 production cost and CO2 emission rate of 7.03 kgH2 −1 and 0.083 kmolCO2 kmolH2 −1 obtained. Abstract : Techno-economic and carbon footprint analysis based on process simulation was conducted to figure out unit H2 production costs and CO2 emission rates under various operating conditions. Optimized operating conditions for minimum H2 production cost were also investigated.